Pedestrians walking speed and psychological distance at bus terminal and shopping mall - Mohamad Ali, Mohd Firdaus (2019)
The studies of pedestrians walking speed and psychological distance in both indoor and outdoor are important for understanding the walking behaviours especially in the Malaysian context. In order to obtain relevant information on pedestrians walking behaviours, it is essential to conduct some investigations on factors that are influencing the walking speed and psychological distances among pedestrians which are age, gender, relationship status, and location. This is because the outcomes can be various due to the difference of the aforementioned factors. In this research, data acquisition was executed using video recording method and the data that were obtained were extracted using a tool named Human Behavior Simulator (HBS) that was plugged-in into Autodesk Maya. Walking speeds were analysed between two locations which are bus terminal and two shopping malls namely Terminal Bersepadu Selatan (TBS), MyTown Shopping Centre and Sunway Velocity Mall. In overall, the fastest walking speed was obtained at bus terminal and the slowest was obtained at shopping mall with the average walking speed of 1.03 m/s and 0.85 m/s respectively. Also, the average walking speed were also affected by three other factors which are gender, age and baggage. Male pedestrians walked averagely 5% to 16% faster than female pedestrians. Meanwhile, male adults walked around 7% to 16% faster than male senior adults while female adults walked around 11% to 22% faster than female senior adults at both bus terminal and shopping malls. Other than that, pedestrians that were walking without carrying baggage were faster within the range of 4% to 13 % in term of percentage than those without carrying baggage. In psychological distance, the factors of relationships and genders had given significant impacts on the results in which the differences that occurred during the observations were around 20% to 56% of gap differences in term of percentage between pedestrians with and without relationship.